Interspecies transmission and emergence of novel viruses: lessons from bats and birds - Chan, Jasper Fuk-Woo; To, Kelvin Kai-Wang; Tse, Herman; Jin, Dong-Yan; Yuen, Kwok-Yung (Trends in microbiology (Regular ed.), 2013)
•Bats and birds are reservoirs of zoonotic viruses.•Their unique immune systems allow them to harbor a large variety of viruses.•Coronaviruses and influenza viruses are examples of interspecies transmission of viruses. As exemplified by coronaviruses and influenza viruses, bats and birds are natural reservoirs for providing viral genes during evolution of new virus species and viruses for interspecies transmission. These warm-blooded vertebrates display high species biodiversity, roosting and migratory behavior, and a unique adaptive immune system, which are favorable characteristics for asymptomatic shedding, dissemination, and mixing of different viruses for the generation of novel mutant, recombinant, or reassortant RNA viruses. The increased intrusion of humans into wildlife habitats and overcrowding of different wildlife species in wet markets and farms have also facilitated the interspecies transmission between different animal species.